Training Of The Student Researcher In Higher Education In Colombia (2022)
Human development is a dimension that concretizes evidence adjusted to social demands from a framework of formation of individuals focused on constructing knowledge from different perspectives. In this sense, the formation of the university research student, the motivation for the exercise of science and innovation, and the pedagogical practices by teachers have presented different curricular problems, which are of the total interest in this research. Its general objective is to generate epistemological reflections that articulate the curriculum and processes of resignification of research training in the context of a university with social relevance. It is carried out under a historical hermeneutic paradigm of qualitative type, using the hermeneutic circle, interview and discussion groups as tools for collecting information with university students of the region evidencing and proposing more current pedagogical bets, the importance of research seedbeds and knowing the main obstacles presented in the research praxis.